Implementasi Etika Profesi Notaris dan PPAT dalam Menjalankan Kewenangan Jabatan - Jufri Yusup (Al-Kindi, 2026)
This study aims to analyze the implementation of professional ethics for Notaries and Land Deed Officials (PPAT) in carrying out their official duties, identify the factors causing violations of the professional code of ethics, and examine the forms of legal responsibility arising from such violations. The research employs a normative legal research method using statutory, conceptual, and case approaches. Data were collected through library research by examining legislation, professional codes of ethics, legal literature, journals, and relevant court decisions. The findings indicate that professional ethics play a fundamental role in ensuring legal certainty, justice, and legal protection in the preparation of authentic deeds. Compliance with the Notary Code of Ethics and the PPAT Code of Ethics, together with adherence to applicable laws and regulations, serves as a preventive mechanism against abuse of authority and procedural violations. The study also reveals that violations of professional ethics are primarily caused by the lack of prudence, weak professional integrity, and non-compliance with legal procedures, resulting in administrative, civil, criminal, and organizational sanctions. Therefore, strengthening supervision, continuous professional education, and consistent enforcement of the code of ethics are essential to maintaining the dignity of the professions and enhancing public trust in Notaries and PPAT.